Hidroksiapatit (HAp) dari Cangkang Kerang Mutiara Air Tawar (Kijing) (Anodonta woodiana) Rawa Pening Kabupaten Semarang - Agung Rimayanto Gintu (LPPM Institut Teknologi Petroleum Balongan, 2022)
Hydroxyapatite (HAp) was one of biomaterials for hard tissues reparation synthesized fromMolluscan shells. In this study treated the synthesis of HAp from Anodonta woodiana clams shells obtainedfrom Rawa Pening Lake, Semarang regency, Central of Java. Physicochemical characterizationsagainst theshells showed Ash contains 0,9985 ± 0,0005g/g; Calcium / CaO 0,4460 ± 0,0082g/g; Calcium / CaCO3 0,1845± 0,0012g/g; and Phosphate 0,1893 ± 0,0102g/g, suitable with the need in HAp synthesic. HAp in this studysynthesized by Base Precipitation method and obtained rendement of synthesis 50,25 ± 0,0384% and HAp withRatio Ca/P 1,4611% based on Bray and 1,3847% by Olsen’s methods; Porosity 50,25 ± 0,0384%;Biodegradability 70,22 ± 0,0203%; Swelling ability 65,28 ± 0,0291%; Density 0,8898 ± 0,0008g/mL; KineticViscosity 1,1986 ± 0,0982CTs; and Mollecular Weight 0,0076 ± 0,0007g/mol. Based on the results concludedthat HAp success synthesized from A. woodiana clams shells by Base Precipitation methods.